Governing 'risky' sexualities: Representation of dementia and sexuality in the news media - Alisa Grigorovich (Disability Studies Quarterly, 2020)
Drawing on critical scholarship on sexuality, disability and gerontology, this paper examines representations of dementia and sexuality across recent North American, European and Australian news media sources. Attending to the affects mobilized within these representations demonstrates how they support the constitution of the sexualities of persons with dementia as dangerous, and thus as requiring surveillance and restriction. I argue that the media stigmatizes persons with dementia by constructing them as either sexual predators or asexual victims. The first construct explicitly incites disgust and fear towards the sexualities of men with dementia, while the second elicits a superficial form of caring towards women with dementia. Such representations preclude the recognition and support of the sexual rights of persons with dementia, including their right to experience sexual pleasure.
Keywords: dementia; sexuality; affect; media